Revisionism and empire : socialist imperialism in Germany 1987-1914 - Fletcher, Roger (London : George Allen & Unwin, 1984)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: imperialisme; socialisme; Duitsland